A bifunctional amino acid to study protein–protein interactions. Issue 69 (18th November 2020) - Yang, Tangpo; Li, Xin; Li, Xiang David
Abstract : dzANA is a novel bifunctional (photo-reactive and bioorthogonal) amino acid to study protein–protein interactions. Abstract : Protein–protein interactions (PPIs) play crucial roles in regulating essentially all cellular processes. Photo-cross-linking represents a powerful method to study PPIs. To fulfil the requirements for the exploration of different PPIs, there is a continuous demand on the development of novel photo-reactive amino acids with diverse structural properties and functionalities. Reported herein is the development of a bifunctional amino acid termed dzANA, which contains a diazirine, for photo-cross-linking, and a terminal alkyne group, for bioorthogonal tagging. Using known PPIs between histone posttranslational modifications (PTMs) and their binding partners as models, we demonstrate that the dzANA -harbouring peptide-based photoaffinity probes could efficiently and selectively capture the weak and transient PPIs mediated by histone modifications. Our study indicates the potential of dzANA to identify and characterize unknown PPIs.